An algorithm for random generation of admissible horizontal alignments for optimum layout design. (21st April 2021) - Vázquez‐Méndez, Miguel E.; Casal, Gerardo; Castro, Alberte; Santamarina, Duarte
Abstract: This work deals with the design of horizontal alignments (HAs) for its application in intelligent civil systems. Two consecutive tasks are performed: the random generation of admissible horizontal alignments (AHAs; alignments verifying some geometric constraints set in advance) and the optimal design of layouts joining two given points. A rigorous mathematical analysis of the first task leads to a novel algorithm for random generation of alignments, which is used to develop the global optimization method proposed for the second task. The usefulness of this approach is shown on some practical applications. First, two problems with applications in robotics, pipe layout design, and forest road design are solved in realistic situations. Next, the random generation of AHAs in mountainous terrain is addressed. Finally, the model is extended to 3D alignments and a real case study is presented, designing a bypass on the N‐640 Spanish national road, surrounding the urban area of Monterroso.